Analytical evaluation of the rapeseed market in Ukraine - Makarchuk, O. G.; Skudlarski, J. (НУБіП України, 2018)
In the article is analysed the rapeseed market in Ukraine. Strengths and weaknesses of the rapeseed market are defined as well as its prospects and threats of the external environment. The balance of rapeseed and its vegetable oil were estimated, in particular the internal processing of rape seeds and further exports, and the use of these products as raw materials for biodiesel. Theoretical and methodological basis of the research are the provisions of economic theory, scientific developments of domestic and foreign scientists, legislative and regulatory acts of Ukraine, as well as statistical data.
Аналітична оцінка ринку ріпака в Україні
Проаналізовано ринок ріпака в Україні. Наведено сильні і слабкі сторони ринку ріпака, а також визначено перспективи і загрози зовнішнього середовища. Оцінено баланс ріпака та олії на його основі для надання обґрунтованих висновків, зокрема внутрішньої переробки насіння для подальшого експорту, а також використання даних продуктів як сировини для біодизелю. Теоретичною і методичною основою дослідження є положення економічної теорії, наукові розробки вітчизняних і зарубіжних вчених, законодавчі та нормативні акти України, а також статистичні дані.
Keywords: rapeseed market; rape oil; Ukraine; balance; export; mport; biodiesel; ринок ріпака; рапсове масло; Україна; експорт; імпорт; біодизель